Polarization Multiplexing Silicon-Photonic Optical Phased Array for 2D Wide-Angle Optical Beam Steering - Xibo Yan; Jingye Chen; Daoxin Dai; Yaocheng Shi (IEEE Photonics Journal, 2021)
We propose the silicon photonic optical phased array (OPA) with large scanning angle by using polarization multiplexing. A Mach-Zehnder interferometer (MZI) switch together with a polarization splitter/rotator is utilized to select the polarization mode input to the OPA. By optimizing the OPA grating emitter, the steering angle can be doubled with the input of the TE/TM polarization modes. An 1 × 16 silicon-based optical phased array with polarization multiplexing is designed as an example. The simulation results show that 77.4° lateral beam steering with no sidelobes via phase tuning and 28.2° longitudinal beam steering via wavelength tuning can be realized.